2022
DOI: 10.7150/jca.65012
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers for predicting the efficacy of immune checkpoint inhibitors

Abstract: Immune checkpoint blockade has vastly changed the landscape of cancer treatment and showed a promising prognosis for cancer patients. However, there is still a large portion of patients who have no response to this therapy. Therefore, it's essential to investigate biomarkers to predict the efficacy of immune checkpoint inhibitors. This article summarizes the predictive value of established biomarkers, including programmed cell death ligand 1(PD-L1) expression level, tumor mutational burden, tumor-infiltrating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 165 publications
(172 reference statements)
0
13
0
Order By: Relevance
“…Additionally, contraindications are based on observations of toxicity risk or tumor hyperprogression. The most common contraindications relevant to lung cancer therapy have been classic activating mutations in EGFR, where prior TKI use has been linked to a long-lasting increased risk of severe and almost always fatal pneumonitis, requiring permanent discontinuation of immunotherapy, with the risk increasing with additionally therapeutic modalities such as radiotherapy [ 80 , 81 ]). Importantly, MDM2 amplification in solid tumors has been associated with the paradoxical tumor hyper-progression seen in patients who receive PD-1/PD-L1 checkpoint blockade [ 82 , 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, contraindications are based on observations of toxicity risk or tumor hyperprogression. The most common contraindications relevant to lung cancer therapy have been classic activating mutations in EGFR, where prior TKI use has been linked to a long-lasting increased risk of severe and almost always fatal pneumonitis, requiring permanent discontinuation of immunotherapy, with the risk increasing with additionally therapeutic modalities such as radiotherapy [ 80 , 81 ]). Importantly, MDM2 amplification in solid tumors has been associated with the paradoxical tumor hyper-progression seen in patients who receive PD-1/PD-L1 checkpoint blockade [ 82 , 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such important factors are tumor-infiltrating lymphocytes, complex myeloid cells, lipid-associated macrophages, cancer-associated fibroblasts ( CAFs ), and other molecules that promote the growth and migration of tumor cells [ 99 ]. Tumor-infiltrating lymphocytes ( TIL ) are considered an important prognostic factor in various types of oncological diseases [ 100 , 101 , 102 , 103 , 104 ] including triple-negative breast cancer ( TNBC ) [ 105 , 106 ]. In general, tumor-infiltrating lymphocytes are strong indicators of tumor immunogenicity [ 107 ]; however, as a heterogeneous population, TILs are associated both with positive and negative outcomes.…”
Section: Tumor Microenvironment Tumor Infiltrating Lymphocytes ( ...mentioning
confidence: 99%
“…Accordingly, there is an urgent need for additional research on new molecular markers that can predict the efficacy of pembrolizumab in patients with advanced BTC. Further studies are needed on peripheral blood cell biomarkers, such as the circulating tumor DNA, peripheral immune cells, peripheral cytokines, peripheral blood T-cell receptors, lactate dehydrogenase, interleukin-8, and soluble PD-L1, to determine the immune checkpoint inhibitor efficacy [ 23 , 24 ]. Many studies report that the biliary tract originates from the primitive gut and has a very similar morphology, particularly in the extrahepatic tract, and many researchers have demonstrated that DCLK1 (Doublecortin-like kinase 1) is a cancer stem cell marker in the intestinal tum [ 25 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%